Functioning problems linked to top disability-causing conditions in Nigeria: A scoping review - Rentia A. Maart; Maria Y. Charumbira; Quinette A. Louw (Rehabilitation Advances in Developing Health Systems)
Background: The need for rehabilitation in Nigeria is expected to increase because of the concerning rise in the prevalence of non-communicable diseases (NCDs). Rehabilitation aims to enhance or restore function in individuals with health conditions. Identifying context- and country-specific functioning problems may assist with strengthening rehabilitation in health systems.